Idea tolerancji religijnej w poglądach i doświadczeniach politycznych Williama Penna (1644-1718) - Robak, Piotr (Acta Universitatis Lodziensis. Folia Historica, 1999)
An idea of the liberty of conscience was one of the most important problems of the modern history. William Penn’s contribution to the development and the realization of the idea in the second period of the 17th century is the subject of the article. William Penn was the English gentleman, the member of the Quaker sect - one of the most radical and spiritual group of nonconformists in England - and the founder of Pennsylvania in the North America. Penn’s opinion on the liberty of conscience was the most significant element of his natural theory of state and laws presented in over 50 treatises and pamphlets. His considerations were concerned with the evangelical principles of Quakers and other protestant and spiritual sects. On the other hand, Penn’s idea was based on the political philosophy and the historical, juridical and economic arguments had belonged to the Christian intellectual tradition and the modern European liberal and rational thought. Penn used the idea of the liberty of conscience for defending Quakers and other dissenters in England as well as on the Old Continent (e.g. in Poland) in the age of the Later Stuarts. He wrote many petitions, letters and bills presented to the kings, the parliaments, the Privy Council and to the magistrates of London and other towns. He also profited from the help and the support of many influential courtiers. Moreover Penn and other Quakers took part in the whig political action during the Exclusion Crisis to make real the religious tolerance in England. The failure of these Quaker activities induced Penn, thanks to Charles II the proprietor of Pennsylvania, to found the ideal state of peace, so called Holy Experiment, in the North America. The idea of the liberty of conscience to all the people which believed in God was one of the constitutional laws organizing the public life of the province. About twenty years later when the political experiences in Pennsylvania showed the necessity of change of the Holy Experiment the principle of the liberty of conscience, however, remained as the lasting element of the constitutional laws and one of the great source of the demographic progress and the wealth of the American colony. Penn’s acting on behalf of nonconformists and on the religious tolerance in England was limited by his belonging to Quakers, the different political aims of his Whig supporters, his principles of faith and in general by the attitude of the court, the parliaments and other public institutions towards the sect. But Penn made a success in Pennsylvania where he had as the founder the considerable contribution to the realization of the liberty of conscience. The late American social and political thought was influenced in significant degree by the principle and the practice of the religious tolerance adopted in the 17th century in the Quaker colony and guaranteed in Penn’s constitutions.